2005
DOI: 10.1016/j.bbrc.2004.11.138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins binding the native tubulin dimer

Abstract: Microtubules play an essential role in eukaryotic cells, where they perform a wide variety of functions.In this paper, we describe the characterization of proteins associated to tubulin dimer in its native form, using affinity chromatography and mass spectrometry. We used an immunoaffinity column with coupled-monoclonal antibody directed against the α-tubulin C-terminus. Tubulin was first loaded onto the column, then interphase and mitotic cell lysates were chromatographed. Tubulin-binding proteins were eluted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
2
17
0
1
Order By: Relevance
“…This analysis allowed us to identify HSP70/GRP75 among the protein associated to TUBB3. This finding supports that GRP78/GRP75 and HSP/HSC70 play the cooperative role of molecular chaperones in formation and function of the eukaryotic cell cytoskeleton (31). Interestingly, we also found that FMO4 forms a complex mediated by disulfide bridges with TUBB3.…”
Section: Discussionsupporting
confidence: 87%
“…This analysis allowed us to identify HSP70/GRP75 among the protein associated to TUBB3. This finding supports that GRP78/GRP75 and HSP/HSC70 play the cooperative role of molecular chaperones in formation and function of the eukaryotic cell cytoskeleton (31). Interestingly, we also found that FMO4 forms a complex mediated by disulfide bridges with TUBB3.…”
Section: Discussionsupporting
confidence: 87%
“…All three proteins have been implicated in cancer progression [32][33][34] and all three bind to cytoskeleton proteins and influence cytoskeleton dynamics and organisation. [35][36][37] In particular, changes in B23 expression alters the balance between stress fibre formation and other more dynamic forms of F actin. 37 Interestingly, Hsp60 and members of the Hsp70 family are also substrates for TG2.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the constitutively expressed isoform of Hsp70, Hsc70/ Hsp73/HSPA8, accounts for 2% of total protein in cells and affects a number of processes including cytoskeletal function and clathrin-mediated endocytosis (14). Hsc70 associates with both intact MTs (15)(16)(17)(18)(19) and tubulin directly through its nucleotidebinding domain (NBD), suggesting functional regulation of tubulin by Hsc70 beyond proteostasis (20). Hsc70 also interacts with the microtubule (MT)-associated protein (MAP) tau, a putative 'typical' client of Hsc70 (6,(21)(22)(23) further suggesting that Hsc70 uniquely regulates MT dynamics (24,25).…”
Section: Introductionmentioning
confidence: 99%